Linguo-philosophical Novations of Russian Symbolism in the Interpretation of L.A. Gogotishvili (Vyach. Ivanov and A.F Losev) - Svetlana V. Fedotova (Studia Litterarum, 2019)
The article discusses the linguo-philosophical novations of Vyach. Ivanov and A.F. Losev in the interpretation of L.A. Gogotishvili, aimed to identify the underlying connections between the two theorists of symbol, myth, and language. It analyzes conceptual approach of the interpreter including the methods and techniques she used. The paper reveals likewise the logic and sequence of the ways these interpretations have been constructed, as well as their nature, originality, and scholarly importance. Gogotishvili’s research contribution to the study of Russian symbolism and onomatodoxy, with its doctrine of language, consists in her seminal understanding of their philosophy of language, as well as of the intellectual “techniques” used by Losev. This understanding helped Gogotishvili to develop her own theoretical approaches to the problem of reception of Ivanov’s symbolism and Losev’s work. In her study of symbolism, Gogotishvili moved from describing the religious status of language in onomatodoxy as well as , its communicative and predicative interpretations, to examining the predicative concept of symbol in Vyach. Ivanov, and then returning to Losev. As a result, here conclusions concerning general features of Ivanov’s and Losev’s novations have undergone some important changes.